P14.02.A Serum neurofilaments correlate with axonal loss in paclitaxel-induced peripheral neurotoxicity. (5th September 2022) - Velasco, R; Marco, C; Mariotto, S; Stradella, A; Hernández, J; Argyriou, A A; Ferrari, S; Bruna, J
Abstract: Background: Paclitaxel-induced peripheral neuropathy (PIPN) is a dose-limiting axonal polyneuropathy. Nerve conduction studies (NCS) are unique for the assessment of axonal impairment in PIPN. Neurofilaments (NFs), constituent of the neuronal cytoskeleton, are emerging as axonal damage biomarker. To date, the association between changes in NCS and NfL quantification across paclitaxel treatment in breast cancer patients has not been specifically addressed. MATERIAL AND METHODS : Prospective longitudinal measurement of sNfL levels and NCS in 27 chemotherapy-naïve breast cancer patients before (V0) and after completion (V1) of 12 cycles of weekly paclitaxel-based therapy. Results: Serum NfL levels (in pg/mL) increased over the course of treatment in the whole of patients (T0: 18, 509 +/- 12, 886 vs T1:255, 805 +/- 194, 165, p<0.001). The increase in sNfL levels at T1 showed a significant moderate correlation with the percentage of decrease in the amplitude of the sural (ρ = 0.6205 (p=0.0035), radial (r=0.6134, p=0.005)), ulnar (ρ = 0.6298 (p=0.005)) and peroneal motor (ρ = 0.5676, p=0.024)) nerve in NCS across treatment. Conclusion: sNfL levels increase proportionally to the degree of paclitaxel-induced neuroaxonal damage, revealing being a promising blood biomarker able to detect the severity of large nerve fiber degeneration and, therefore, improving the diagnostic accuracy in PIPN.